Factors influencing implementation of a patient decision aid in a developing country: an exploratory study - Tong, Wen Ting; Lee, Yew Kong; Ng, Chirk Jenn; Lee, Ping Yein (Med Central, 2017)
Background: Most studies on barriers and facilitators to implementation of patient decision aids (PDAs) are conducted in the west; hence, the findings may not be transferable to developing countries. This study aims to use a locally developed insulin PDA as an exemplar to explore the barriers and facilitators to implementing PDAs in Malaysia, an upper middle-income country in Asia. Methods: Qualitative methodology was adopted. Nine in-depth interviews (IDIs) and three focus group discussions (FGDs) were conducted with policymakers (n = 6), medical officers (n = 13), diabetes educators (n = 5) and a nurse, who were involved in insulin initiation management at an academic primary care clinic. The interviews were conducted with the aid of a semi-structured interview guide based on the Theoretical Domains Framework. The interviews were audio-recorded, transcribed verbatim and analyzed using a thematic approach. Results: Five themes emerged, and they were lack of shared decision-making (SDM) culture, role boundary, lack of continuity of care, impact on consultation time and reminder network. Healthcare providers’ (HCPs) paternalistic attitude, patients’ passivity and patient trust in physicians rendered SDM challenging which affected the implementation of the PDA. Clear role boundaries between the doctors and nurses made collaborative implementation of the PDA challenging, as nurses may not view the use of insulin PDA to be part of their job scope. The lack of continuity of care might cause difficulties for doctors to follow up on insulin PDA use with their patient. While time was the most commonly cited barrier for PDA implementation, use of the PDA might reduce consultation time. A reminder network was suggested to address the issue of forgetfulness as well as to trigger interest in using the PDA. The suggested reminders were peer reminders (i.e. HCPs reminding one another to use the PDA) and system reminders (e.g. incorporating electronic medical record prompts, displaying posters/notices, making the insulin PDA available and visible in the consultation rooms). Conclusions: When implementing PDAs, it is crucial to consider the healthcare culture and system, particularly in developing countries such as Malaysia where concepts of SDM and PDAs are still novel.